RENCANA PENGOPERASIAN STASIUN BARRU (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
Barru Station is planned to be operational in October 2022 with the Maros – Barru line. With this, the Barru Station building must be ready and in accordance with existing regulations so that when operating, passengers can feel comfortable using this station. The station operation plan must be supported by minimum service standards in accordance with applicable regulations, in which the fulfillment of minimum service standards must be adjusted to the classification of station space zoning and also the entry and exit of passengers to support transportation services. From the observations, it was found that many buildings and facilities of the Barru Station were still not in accordance with the applicable regulations. From the research conducted, it can be concluded that the space zoning at Barru Station is divided into 3 zones, the passenger flow is made so that the passengers run according to their respective routes, the facilities that must be perfected include increasing the number of toilets, widening the prayer room, adding the platform canopy, and adding nursing room. ABSTRAKStasiun Barru direncanakan akan beroperasi pada Bulan Oktober 2022 dengan lintas Maros – Barru. Dengan adanya hal tersebut, maka bangunan Stasiun Barru harus siap dan sesuai dengan peraturan yang ada supaya pada saat beroperasi penumpang bisa nyaman menggunakan stasiun ini. Rencana pengoperasian stasiun harus didukung standar pelayanan minimum sesuai peraturan yang berlaku, dimana dalam pemenuhan standar pelayanan minimum harus disesuaikan dengan klasifikasi pembagian zonasi ruang stasiun dan juga alur keluar masuk penumpang demi mendukung pelayanan transportasi. Dari hasil pengamatan, ditemukenali banyak bangunan dan fasilitas Stasiun Barru yang masih belum sesuai dengan peraturan yang berlaku. Dari penelitian yang dilakukan, dapat disimpulkan bahwa zonasi ruang di Stasiun Barru dibagi menjadi 3 zona, alur penumpang dibuat agar penumpang berjalan sesuai alurnya masing-masing, fasilitas yang harus sempurnakan antara lain, penambahan jumlah toilet, pelebaran musholla, penambahan kanopi peron, dan penambahan ruang ibu menyusui.